Comparative study of hatchability rate and egg quality between different strains of Japanese Quail (Coturnix japonica) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The objectives of this study were to determine morphology of Japanese quail strains and hatchability rate and egg quality between commercial strain which is Poultry Progress Institute (IKTA) strain and White Texas strains of Japanese Quail (Coturnix japonica) rear in Malaysia. A total of 300 quails were randomly picked and the breastbone length, chest girth, body weight, body length, shank length and drum length were measured for the morphology. Then, 270 eggs of Commercial and White Texas strains were used to test the hatchability rate (n=150) and egg quality (n=120). The ratio of the parents of the quails between male and female of each type of strain were 1:3. The cleanliness, shape, weight, and texture of the eggshell were observed, weighed and measured. The eggs were incubated for 17 days (37.6 °C, 65% humidity). The shape index, egg weight, egg volume and eggshell surface were weighed and measured for the exterior trait of eggs. For interior trait, the albumen index, Haugh units, and internal quality units (IQU) were measured. Significant findings were observed in all of the features (P